2013
DOI: 10.1038/nn.3500
|View full text |Cite|
|
Sign up to set email alerts
|

Parthanatos mediates AIMP2-activated age-dependent dopaminergic neuronal loss

Abstract: The defining pathogenic feature of Parkinson’s disease is the age dependent loss of dopaminergic neurons. Mutations and inactivation of parkin, an ubiquitin E3 ligase, cause Parkinson’s disease through accumulation of pathogenic substrates. Here we show that transgenic overexpression of the parkin substrate, aminoacyl-tRNA synthetase complex interacting multifunctional protein-2 (AIMP2) leads to a selective, age-dependent progressive loss of dopaminergic neurons via activation of poly(ADP-ribose) polymerase-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
234
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(241 citation statements)
references
References 52 publications
7
234
0
Order By: Relevance
“…IHC was performed as described previously (26,56). Mice were intracardially perfused with ice-cold PBS and 4% paraformaldehyde/PBS (wt/vol, pH 7.4) after deep anesthesia by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…IHC was performed as described previously (26,56). Mice were intracardially perfused with ice-cold PBS and 4% paraformaldehyde/PBS (wt/vol, pH 7.4) after deep anesthesia by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…30,39,43 This study shows that FAF1 is essential for PARP1-dependent necrosis in response to oxidative stress, in which caspases are not activated. However, caspase-mediated apoptosis has also been found to occur in relation to the pathogenesis of PD, and the oxidative stress-induced damage in a mouse model of PD has been found to be reduced by treatment with caspase inhibitors, suggesting that caspase inhibition is also a plausible strategy for PD treatment.…”
Section: Discussionmentioning
confidence: 70%
“…The PARP1 activity can be regulated by the physical interaction of PARP1 with its binding partner. 39,40 Given that FAF1 interacts with PARP1, we examined whether the PARP1 activity might be regulated by FAF1. We found that FAF1 overexpression induced a dose-and timedependent increase in the PAR polymer in response to Figure S6a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations